Metacide : in the pursuit of excellence - Watson, James R. (Value Inquiry Book Series, 2010)
If philosophy addresses concrete ethical challenges, then what shifts in basic concepts must be made to the discipline in the darkness of our genocidal world? What anti-genocidal strains are in Western philosophy? Are we "really" rejects and/ or "still of intrinsic worth" when we fail our excellence tests? How are we represented and how do we participate in representations? Are representational forms historical in origin and development? Is genocide indissolubly linked to our degradation and destruction of animals? Can one slaughter and eat one's partners in a social bond? If so, what does this tell us about the socio-political world we have formed? Is there a deep center-metacide-in our culture from which genocide receives its impulse? These are some of the pivotal questions addressed in the thirteen thought-provoking essays of this volume.